Efficacy of invasive alien plants in controlling Arionidae slugs - Laznik, Ziga; Bohinc, Tanja; Franin, Kristijan; Majić, Ivana; Trdan, Stanislav (Spanish Journal of Agricultural Research, 2020)
Aim of study: To develop an alternative slug control method, we explored the use of plant material from seven invasive plant species against Arion slugs.Area of study: The experiments were performed at the University of Ljubljana (Slovenia).Material and methods: In laboratory (exp. A-C) and semi-field studies (exp. D), we investigated the contact and barrier efficacy of plant material (powder or liquid formulation) of seven invasive plant species (Japanese knotweed, bohemian knotweed, Canadian goldenrod, giant goldenrod, staghorn sumac, tree of heaven, and false indigo) against Arion slugs. In order to test a contact efficacy of the substance (exp. A), slugs were rolled in a plant material powder. In exp. B, powder made from a plant material was used as a barrier for slugs. Antifeedant effect of the slugs was tested in exp. C, where lettuce leaves were treated with a liquid formulation of a plant material. In exp. D, all above mentioned techniques were used in a semi-field trial.Main results: The results of our studies showed that the plant material of staghorn sumac, giant goldenrod, and Japanese knotweed showed the strongest anti-feedant and barrier effects against the slugs. In the semi-field trial, only 7% of the plants treated with giant goldenrod plant material were attacked by slugs.Research highlights:  A contact efficacy of plant powders against Arion slugs was not confirmed in our investigation. Furthermore, several plant powders (goldenrods, staghorn sumac) showed good barrier efficacy. A semi-field trial showed that plant material (giant goldenrod) could represent an alternative solution in slug control.